2016
DOI: 10.1175/jhm-d-15-0164.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ShARP Passive Rainfall Retrievals over Snow-Covered Land Surfaces and Coastal Zones

Abstract: For precipitation retrievals over land, using satellite measurements in microwave bands, it is important to properly discriminate the weak rainfall signals from strong and highly variable background surface emission. Traditionally, land rainfall retrieval methods often rely on a weak signal of rainfall scattering on high-frequency channels (85 GHz) and make use of empirical thresholding and regression-based techniques. Due to the increased ground surface signal interference, precipitation retrieval over radiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Satellite-based precipitation datasets are expected to provide improved estimates of the global precipitation and enhance the accuracy of the reanalysis products. However, passive microwave satellite data are not free of error, especially over complex topography where the microwave signal of shallow precipitation is weak (Ebtehaj et al 2016). For example, intercomparison studies over Europe have shown that satellite products have a tendency to overestimate precipitation over flat regions and underestimate it over mountainous regions (Prein and Gobiet 2017).…”
Section: B Precipitationmentioning
confidence: 99%
“…Satellite-based precipitation datasets are expected to provide improved estimates of the global precipitation and enhance the accuracy of the reanalysis products. However, passive microwave satellite data are not free of error, especially over complex topography where the microwave signal of shallow precipitation is weak (Ebtehaj et al 2016). For example, intercomparison studies over Europe have shown that satellite products have a tendency to overestimate precipitation over flat regions and underestimate it over mountainous regions (Prein and Gobiet 2017).…”
Section: B Precipitationmentioning
confidence: 99%
“…In principle, the separation and search of the a priori database by the EPC‐based method applies similar reasoning as other empirically based retrievals (Petty and Li, ; ; Ebtehaj et al ., ), the common factor being that the TB observations (or transformations involving the TB) play a much more direct role in the selection and weighting of a priori candidates. The EPC is essentially based upon the obscuration of the surface emissivity signal as clouds and precipitation enter the scene.…”
Section: Discussionmentioning
confidence: 99%
“…A surface emissivity-based a priori database indexing scheme that incorporates information directly from the TB observations may be advantageous for precipitation retrievals to better transition across oceanic, land, and the complex nature of mixed land-water and land-ice scenes, with minimal surface-related artefacts in the resultant precipitation products. The Shrunken Locally Linear Embedding Algorithm for Retrieval of Precipitation (ShARP) embeds TB spectral surface information within its a priori database search and has demonstrated improvements to the detection and estimation of precipitation across complex coastal and snow cover scenes (Ebtehaj et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The nearest neighbor matching has been successfully utilized for passive microwave retrieval of rainfall using the TRMM data (Ebtehaj et al, 2015(Ebtehaj et al, , 2016 and for microwave mapping of flood inundation using the Special Sensor Microwave Imager/Sounder observations (Takbiri et al, 2017). In this section, we introduce a prognostic algorithm that relies on a nested k-nearest neighbor matching that finds the best representation of a query brightness temperature in the database to detect precipitation occurrence and phase.…”
Section: A Nested Nearest Neighbor Algorithm For Precipitation Phase ...mentioning
confidence: 99%